Mechanistic Insights Underlying Tolerance to Acetic Acid Stress in Vaginal Candida glabrata Clinical Isolates - Cunha, Diana V.; Salazar, Sara B.; Lopes, Maria M.; Mira, Nuno P. (Frontiers in Microbiology, 2017)
During colonization of the vaginal tract Candida glabrata cells are challenged with the presence of acetic acid at a low pH, specially when dysbiosis occurs. To avoid exclusion from this niche C. glabrata cells are expected to evolve efficient adaptive responses to cope with this stress; however, these responses remain largely uncharacterized, especially in vaginal strains. In this work a cohort of 18 vaginal strains and 2 laboratory strains (CBS138 and KUE100) were phenotyped for their tolerance against inhibitory concentrations of acetic acid at pH4. Despite some heterogeneity has been observed among the vaginal strains tested, in general these strains were considerably more tolerant to acetic acid than the laboratory strains. To tackle the mechanistic insights behind this differential level of tolerance observed, a set of vaginal strains differently tolerant to acetic acid (VG281~VG49<VG99<VG216) and the highly susceptible laboratory strain KUE100 were selected for further studies. When suddenly challenged with acetic acid the more tolerant vaginal strains exhibited a higher activity of the plasma membrane proton pump CgPma1 and a reduced internal accumulation of the acid, these being two essential features to maximize tolerance. Based on the higher level of resistance exhibited by the vaginal strains against the action of a β-1,3-glucanase, it is hypothesized that the reduced internal accumulation of acetic acid inside these strains may originate from them having a different cell wall structure resulting in a reduced porosity to undissociated acetic acid molecules. Both the vaginal and the two laboratory strains were found to consume acetic acid in the presence of glucose indicating that metabolization of the acid is used by C. glabrata species as a detoxification mechanism. The results gathered in this study advance the current knowledge on the mechanisms underlying the increased competitiveness of C. glabrata in the vaginal tract, a knowledge that can be used to guide more suitable strategies to treat infections caused by this pathogenic yeast.